Bacteria inactivation by sulfate radical: progress and non-negligible disinfection by-products - Zhou, Xin; Ren, Xiaoya; Chen, Yu; Feng, Haopeng; Yu, Jiangfang; Peng, Kang; Zhang, Yuying; Chen, Wenhao; Tang, Jing; Wang, Jiajia; Tang, Lin (Frontiers of environmental science & engineering, 2023)
● Status of inactivation of pathogenic microorganisms by SO 4 *− is reviewed. ● Mechanism of SO 4 *− disinfection is outlined. ● Possible generation of DBPs during disinfection using SO 4 *− is discussed. ● Possible problems and challenges of using SO 4 *− for disinfection are presented. Sulfate radicals have been increasingly used for the pathogen inactivation due to their strong redox ability and high selectivity for electron-rich species in the last decade. The application of sulfate radicals in water disinfection has become a very promising technology. However, there is currently a lack of reviews of sulfate radicals inactivated pathogenic microorganisms. At the same time, less attention has been paid to disinfection by-products produced by the use of sulfate radicals to inactivate microorganisms. This paper begins with a brief overview of sulfate radicals' properties. Then, the progress in water disinfection by sulfate radicals is summarized. The mechanism and inactivation kinetics of inactivating microorganisms are briefly described. After that, the disinfection by-products produced by reactions of sulfate radicals with chlorine, bromine, iodide ions and organic halogens in water are also discussed. In response to these possible challenges, this article concludes with some specific solutions and future research directions.